Tussilago farfara L.: Antioxidant and antibacterial potential of extracts in in vitro conditions - Emir Horozić; Kolarević Lamija; Edina Huseinović; Darja Husejnagić; Merima Ibišević; Enida Karić; Ermina Cilović-Kozarević; Suada Cipurković (Institute of Computer Science (IOCS), 2023)
Tussilago farfara L., also known as coltsfoot, is a plant that has been used since ancient times to relieve coughs. Subsequently, the effectiveness of coltsfoot in the treatment of bronchial asthma, pneumonia and other respiratory diseases was established. In this research, the antioxidant and antimicrobial activity of different coltsfoot extracts was analyzed. The antioxidant activity was monitored through the DPPH radical inhibition efficiency and the extract's reducing ability. Antibacterial activity was tested using the diffusion technique. Tussilago farfara L. extracts showed extremely high antioxidant activity in in vitro conditions. The highest antioxidant capacity was found in extracts prepared by mixing water and organic solvents. High antibacterial activity was found for ethanolic, acetone and aqueous-ethanolic extracts of coltsfoot.